2018
DOI: 10.1038/s41598-018-25263-5
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 Decreases Tumorigenesis in Group 3 Medulloblastoma Patient-Derived Xenografts

Abstract: Group 3 tumors account for 28% of medulloblastomas and have the worst prognosis. FTY720, an immunosuppressant currently approved for treatment of multiple sclerosis, has shown antitumor effects in several human cancer cell lines. We hypothesized that treatment with FTY720 (fingolimod) would decrease tumorigenicity in medulloblastoma patient-derived xenografts (PDXs). Three Group 3 medulloblastoma PDXs (D341, D384 and D425) were utilized. Expression of PP2A and its endogenous inhibitors I2PP2A and CIP2A was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…This suggested that the immunomodulatory drug might be repurposed as an anti-tumor agent (Enjeti, D'Crus, Melville, Verrills, & Rowlings, 2016; Patmanathan, Yap, Murray, & Paterson, 2015; Rincon et al, 2015). FTY720 itself displayed promising effects in several pre-clinical cancer models (Baldacchino et al, 2014; Cristobal et al, 2014; Cristobal et al, 2016; Garner et al, 2018; Neviani et al, 2007; Oaks et al, 2013; Ramaswamy, Spitzer, & Kentsis, 2015; Szymiczek et al, 2017; Velmurugan et al, 2018; Wallington-Beddoe et al, 2012; Wallington-Beddoe, Hewson, Bradstock, & Bendall, 2011; Zonta et al, 2015). In some cases it overcame resistance to kinase inhibitors and chemotherapeutics that are commonly used as first line cancer treatments (Kiyota et al, 2013; McDermott et al, 2014; Neviani et al, 2013; Perrotti & Neviani, 2006; Rincon et al, 2015; Smith et al, 2016), indicating that combination therapies incorporating FTY720 or other PADs may be highly promising (Mazhar, Taylor, Sangodkar, & Narla, 2019).…”
Section: Pp2a and Cancermentioning
confidence: 99%
“…This suggested that the immunomodulatory drug might be repurposed as an anti-tumor agent (Enjeti, D'Crus, Melville, Verrills, & Rowlings, 2016; Patmanathan, Yap, Murray, & Paterson, 2015; Rincon et al, 2015). FTY720 itself displayed promising effects in several pre-clinical cancer models (Baldacchino et al, 2014; Cristobal et al, 2014; Cristobal et al, 2016; Garner et al, 2018; Neviani et al, 2007; Oaks et al, 2013; Ramaswamy, Spitzer, & Kentsis, 2015; Szymiczek et al, 2017; Velmurugan et al, 2018; Wallington-Beddoe et al, 2012; Wallington-Beddoe, Hewson, Bradstock, & Bendall, 2011; Zonta et al, 2015). In some cases it overcame resistance to kinase inhibitors and chemotherapeutics that are commonly used as first line cancer treatments (Kiyota et al, 2013; McDermott et al, 2014; Neviani et al, 2013; Perrotti & Neviani, 2006; Rincon et al, 2015; Smith et al, 2016), indicating that combination therapies incorporating FTY720 or other PADs may be highly promising (Mazhar, Taylor, Sangodkar, & Narla, 2019).…”
Section: Pp2a and Cancermentioning
confidence: 99%
“…In a growing number of studies, pharmacological inhibition of SET has been achieved by means of two well-studied inhibitors of SET, FTY720 24 , 31 33 and COG112 28 , 40 . FTY720 is a sphingosine immunosuppressant drug which has been shown to have anti-tumor properties in different human malignancies 31 , 32 , including Hh-dependent medulloblastoma 33 . The interaction of FTY720 with SET is direct and has been studied in detail by distinct and complementary approaches, including molecular modelling 31 , biochemical binding assays 31 and recently by NMR experiments 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have focused on SET targeting as a potential therapeutic approach in cancer 28 , 29 , by testing the effects of two SET inhibitors, COG112 28 , 30 and FTY720 24 , 31 33 on cancer progression. COG112 is an apolipoprotein E (apoE)-mimetic peptide which inhibits SET-Rac1 interaction resulting to decreased cell migration and invasion of cancer cells 28 , 30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated data suggest that the sensitivity to standard chemotherapeutics in PDXs closely correlates with clinical data for patients from which the PDXs are derived [127,130]. The PDX has been used for many different cancers, including colon adenocarcinoma [1,131], pancreatic cancer [132,133], cholangiocarcinoma [134], glioblastoma [135], glioma [136], medulloblastoma [137], breast carcinoma [130,138,139], lung cancer [140], malignant melanoma [141], head and neck squamous cell carcinoma (HNSCC) [142], ovarian cancer [143,144], and bladder cancer [145].…”
Section: Patient-derived Xenograft (Pdx) Modelsmentioning
confidence: 99%